Reactivity of Some Heterocyclic Ketone Thiosemicarbazones towards Chloramine-T: A Kinetic and Mechanistic Study - Venkateswaran, V.; Asaithambi, M. (Asian Journal of Chemistry, 2016)
Kinetics of oxidation of piperidinone thiosemicarbazones (PTSC) by Chloramine-T (CAT) in aqueous acetic acid medium have been investigated in the presence of perchloric acid. Oxidation of all the substrates showed first order kinetics in [CAT] and fractional order in [PTSC]. The reactions show inverse fractional order dependence on [H3O+]. Variation in ionic strength of the medium and addition of the reduced product of the oxidant, viz., p-toluene-sulphonamide have only negligible effect on the rate of oxidation. The rate of reaction increases with decrease in the dielectric constant of the medium. Added acrylamide fails to polymerize eliminating the possibility of free radical pathway for the reaction. The stoichiometry of the reaction and the product analysis have also been carried out. From the kinetic data obtained at different temperatures the various activation parameters have been computed and a plausible mechanism proposed.